Analyses Of Complex Topological And Surficial Features Retrieved From Contour Based Digital Elevation Models (DEMs) And Remotely Sensed Data - Chockalingam, L. (2005)
This thesis carries out a thorough characterisation of networks and planar forms of hillslopes surrounded by channels that traverse along topographic minima positions. the work combines spatial analysis of networks that are simulated and / or extracted from digital elevation models, and ideas based on theory of mathematical morphology to reconstruct basins and further generated planar forms of hillslopes within a basin.